2019
DOI: 10.1002/jmv.25642
|View full text |Cite
|
Sign up to set email alerts
|

VP7 and VP4 genotypes of rotaviruses cocirculating in Iran, 2015 to 2017: Comparison with cogent sequences of Rotarix and RotaTeq vaccine strains before their use for universal mass vaccination

Abstract: The present study was conducted to analyze the genotypic diversity of circulating species A rotavirus (RVA) strains in Iran and also to investigate comparative analysis between the genotypes of VP4 and VP7 of cocirculating RVA and vaccine strains before the vaccine is introduced in the national immunization program. The G3‐lineage I was found in this study as the most common G genotype which was followed by G9‐lineage III, G1‐lineages I, II, G12‐lineage III, G2‐lineage IV, and G4‐lineage I. Also, P[8]‐lineages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 65 publications
6
16
0
1
Order By: Relevance
“…analyses of P[8] sequences from the global RVA database, P[8] clustered into four separate evolutionary lineages: P[8]-lineage I, P[8]-lineage II, P[8]-lineage III, and P[8]-lineage IV 38. In the line with our previous finding,25,39 most of the Iranian strains clustered in P[8]-lineage III, which differed from the vaccination strain lineages (Rotarix TM and RotaTeq TM ), which grouped in P[8]-lineages I and II, respectively. Lineage IV strains, which have also been found in Iranian strains, have recently gained interest because they are now being detected all around the world after initially being discovered in Malawi 40.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…analyses of P[8] sequences from the global RVA database, P[8] clustered into four separate evolutionary lineages: P[8]-lineage I, P[8]-lineage II, P[8]-lineage III, and P[8]-lineage IV 38. In the line with our previous finding,25,39 most of the Iranian strains clustered in P[8]-lineage III, which differed from the vaccination strain lineages (Rotarix TM and RotaTeq TM ), which grouped in P[8]-lineages I and II, respectively. Lineage IV strains, which have also been found in Iranian strains, have recently gained interest because they are now being detected all around the world after initially being discovered in Malawi 40.…”
supporting
confidence: 85%
“…Overall, it has been indicated that the most predominant VP7 genotype was G1 in past years, although some studies sporadically reported the prevalence of the G3, G4, G8, and G9 strains, showing RVA G genotype distributions fluctuated both geographically and temporally in the absence of RVA vaccination 24–31 24,25,30 . As mentioned, the P [8] strain is the main vaccine target included in both RVA vaccines, and also P[8] strain still continues a mostly dominant P genotype in Iran.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…which would prevent neutralizing antibody activity [49]. Substitution (K238N) was previously identified in Belgian [48], Iranian [50], Russian [51] and Tunisian [52] strains. Amino acid changes at residues 100, 146,148,150,188,190,194,180,183,114,116,133,135,87,88,89 have been shown to cause escape from neutralization with monoclonal antibodies [53].…”
Section: Plos Onementioning
confidence: 99%
“…Многочисленные работы посвящены сравнительному анализу области нейтрализующих эпитопов белков VP7 и VP4 у РВА, изолированных на разных территориях, и вакцинных штаммов RV1 и RV5 [35][36][37]. Однако подобные исследования не проводятся в отношении белка VP6, в связи с чем мы провели сравнение аминокислотного состава области антигенных эпитопов белка VP6 штаммов в составе RV1 и RV5 и ротавирусов, изолированных на территории РФ после 2010 г. Анализ аминокислотного состава в области антигенных эпитопов VP6 указывает на высокую консервативность антигенных детерминант у вакцинных штаммов и штаммов дикого типа, изолированных на территории РФ, несмотря на разницу во времени их выделения.…”
Section: Discussionunclassified